2015
DOI: 10.1002/etep.2080
|View full text |Cite
|
Sign up to set email alerts
|

Research on forced oscillations disturbance source locating through an energy approach

Abstract: Summary Low‐frequency oscillations (LFOs) are inherent phenomena of modern interconnected electrical power systems, essentially caused by the continuous exchange of momentum among rotating masses. It is widely recognized that LFOs can be induced by both the occurrence of multiple disturbances and the existence of periodic disturbance sources. LFOs can be classified into negative damped oscillations and forced power oscillations. The former can be suppressed by standard controllers (e.g., power system stabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Another phenomenon called the concentric relaxation is introduced in [51] for power systems under forced oscillations, which could help avoid the erroneous location results. To date, this category of methods has been largely applied to power systems in the past five years [52][53][54][55][56][57][58][59][60][61][62][63].…”
Section: Energy Based Methodsmentioning
confidence: 99%
“…Another phenomenon called the concentric relaxation is introduced in [51] for power systems under forced oscillations, which could help avoid the erroneous location results. To date, this category of methods has been largely applied to power systems in the past five years [52][53][54][55][56][57][58][59][60][61][62][63].…”
Section: Energy Based Methodsmentioning
confidence: 99%
“…Besides poorly damped oscillation, it is well recognized that there is another common type of low‐frequency oscillation, known as forced oscillation. Extensive research has been reported on the subject …”
Section: Introductionmentioning
confidence: 99%
“…More specifically, methods for locating forced oscillation sources are proposed recently in the literatures . Wang and Sun gives a comprehensive review of the location methods and elaborates on their advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations